WORKSHOP PENYUSUNAN PROPOSAL PENELITIAN TINDAKAN KELAS DAN ARTIKEL ILMIAH PADA GURU BK SMA/MA DI KABUPATEN BANTUL - Esti Setiawati; Salamah -; Tarto - (LPPM IST AKPRIND Yogyakarta, 2018)
Research activities and the writing of scientific articles still become obstacles for some teachers for promotion, because the two activities are still perceived difficult. Capturing the difficulties, a team of devotion to the UPY graduate community in cooperation with MGBK SMA/MA conducted a workshop on writing a PTK proposal and a scientific article for teachers of BK SMA/MA in Bantul District. This dedication to the community aims to improve the professionalism of the teachers of BK SMA/MA in Bantul regency, especially the preparation of research proposals for class action and the writing of scientific papers. Methods of the workshop activities are carried out through: material delivery activities with varying lectures, class discussions, question and answer, clinics and mentoring of proposal preparation, and presentation of proposals from workshop participants; (2) providing training on the preparation of classroom action research instruments; (3) providing training on the writing of classroom action research reports; and (4) training in writing scientific papers. The first day of training was attended by 30 (thirty) people and the second day was attended by 24 (twenty four) high school teachers of SMA/MA who joined in MGBK SMA/MA in Bantul District. Based on the observations and responses of the workshop participants, the results of the activities are: (1) the teacher's understanding of the classroom action research methodology is further improved, (2) the teacher's understanding of the classroom action research instrument is increasing, (3) the teacher's understanding of writing more class action reports increased, and (4) teachers' understanding of the writing of scientific papers also increased. Beyond this, there is also an increase in cooperation with the Bantul Secondary Education Hall and MGBK SMA/MA in Bantul District.